In vivo anti-inflammatory and in vitro antioxidant potential of leaf and bark fractions of Holoptelea integrifolia (Roxb.) Planch. - Prerna Sharma; Mahadevan Nanjaian; Sanjeev Kalra; Kumarappan Chidambaram (GarVal Editorial Ltda., 2019)
Context: Holoptelea integrifolia is most widely used as a traditional ethnomedicine in India by the local tribal, especially for the treatment of hyperglycemia and as an anti-inflammatory drug. Aims: To evaluate the acute oral toxicity, in vivo anti-inflammatory and in vitro antioxidant therapeutic potential of chloroform and n-butanol fractions of H. integrifolia barks and leaves using appropriate experimental models. Methods: Acute oral toxicity of chloroform and n-butanol fractions were evaluated by 423-acute toxic class method using OECD guidelines. The anti-inflammatory effect of chloroform and n-butanol fractions of H. integrifolia barks (CHIB) and leaves (CHIL) were evaluated at 400 mg/kg (po) on carrageenan-induced hind paw edema in Wistar rats. The observed anti-inflammatory effect was compared to the reference drug, indomethacin (10 mg/kg). The total reducing power of both fractions was determined in vitro and the results were compared with ascorbic acid. Results: The TLC analysis of the bark and leaf extracts revealed the presence of beta-sitosterol. The results of the evaluation of the anti-inflammatory activity of CHIB and CHIL fractions showed a time-dependent reduction of carrageenan-induced paw edema in statistical analysis. In addition, chloroform fraction of H. integrifolia was found to show notable antioxidant activity against hydrogen peroxide radicals scavenging. Conclusions: Experimentally studied CHIB and CHIL possessed interesting anti-inflammatory and antioxidant potential without inducing any apparent acute toxic properties. These pharmacological effects may be attributed, at least in part, to the presence of phenolic compounds/steroidal terpenoids. These results provide scientific support for the traditional use of H. integrifolia in the management of various inflammatory diseases.